China’s Peasants and Workers: Changing Class Identities, Beatriz Carrillo y David S.G. Goodman. - Hernández Hernández, Roberto (México y la Cuenca del Pacífico, 2015)
Reseña del libro: China’s Peasants and Workers: Changing Class Identities (2012), Beatriz Carrillo y David S. G. Goodman, University of Sydney, Australia.